Modelling of Yield and Distribution Coefficient in a Liquid-Liquid Extraction: Effect of the Concentration of Ligand - Hadj Seyd, A.; Lanez, T.; Belfar, M.L. (Asian Journal of Chemistry, 2012)
This work is a contribution to the development of model equations to simulate the yield and the distribution coefficient in a liquid-liquid extraction of formic acid from an aqueous solution. Three cases were studied: (i) the acid is the only constituent in the initial solution, (ii) a mixture of formic acid and benzoic acid, (iii) a mixture of formic acid and ammonia. In each case, the values of the distribution coefficient and the yield of extraction calculated by our models were compared with experimental values. It should be noted that at fixed pH the highest yield of extraction is obtained when the solution contains only a single acid, the yield decreases if the solution contains a mixture of acids and/or bases. We also studied the influence of pH of the solution on the yield and on the distribution coefficient of the extraction over a wide range of pH values from 1.5-11.0.